Alteration reactions which affect the geochemistry of kimberlite and its xenoliths, and the search for unaltered mantle materials - Berg, Gerhard Wolfgang (Department of Geological Sciences, 2024)
[Volume 1 - needs to have volume 2 incorporated.] This thesis records a series of attempts to elicit from bulk kimberlites and their xenoliths, geochemical and mineralogical information meaningful with respect to the primary composition of their source in the mantle. Some of these attempts were successful and some controversial, whilst others were modified significantly to cater for secondary alteration processes (metasomatic events) which took place either in the mantle, or during, or after the emplacement of the rocks in the crust. These secondary events document those stages of the history of the rocks which overwrite and disguise their primary state. It is important to understand the details of these secondary alteration processes so that their record is not erroneously attributed to the primary state of the rocks in the mantle.